The Influence of Transformational Leadership, Job Satisfaction, and Organizational Commitment on Employee Performance - Setia Permana; Firman Dera; Ramdan Yusuf; Noorhani Dyani Laksmi (Journal Management & Economics Review (JUMPER), 2026)
This study aims to examine the influence of transformational leadership, job satisfaction, and organizational commitment on employee performance. In today's competitive organizational environment, improving employee performance is essential for achieving organizational effectiveness and sustainability. Transformational leadership is considered an important leadership approach that inspires employees to achieve higher levels of performance, while job satisfaction and organizational commitment are key psychological factors that influence employees’ attitudes and behaviors in the workplace. This study employs a quantitative research approach with an explanatory research design to analyze the relationships among the variables. Data were collected through a structured questionnaire distributed to employees using a Likert scale measurement. A total of 200 respondents participated in this study. The data were analyzed using Structural Equation Modeling with the Partial Least Squares (SEM-PLS) technique. The results indicate that transformational leadership has a positive and significant influence on employee performance. Job satisfaction also shows a positive and significant effect on employee performance, indicating that satisfied employees tend to demonstrate higher productivity and effectiveness in their work. Furthermore, organizational commitment significantly contributes to employee performance by strengthening employees’ loyalty and dedication toward organizational goals. The coefficient of determination results show that transformational leadership, job satisfaction, and organizational commitment collectively explain a substantial proportion of the variance in employee performance. These findings highlight the importance of effective leadership practices and positive employee attitudes in improving organizational performance. Therefore, organizations should focus on fostering transformational leadership, enhancing job satisfaction, and strengthening organizational commitment in order to improve employee performance and achieve sustainable organizational success.